Higher Subjective Burden in Psychiatric Compared to Somatic Healthcare Workers in Germany During the first wave of the COVID-19 Pandemic - Halms, Theresa; Thoma, Andreas; Kramer, Victoria; Kunz, Miriam; Falkai, Peter; Schneider-Axmann, Thomas; Hierundar, Anke; Wagner, Elias; Hasan, Alkomiet; Papazova, Irina (Fortschritte der Neurologie · Psychiatrie, 2023)
The COVID-19 pandemic has posed unprecedented challenges for health care workers (HCWs) worldwide. While the adverse effects of the pandemic on the well-being of HCWs in general have now been established, little is known about the impact on HCWs of psychiatric hospitals (PHCWs). PHCWs are of special interest, given that they faced both an increase in infection rates among psychiatric patients as well as in mental strain of the general public due to consequences of the pandemic. The aim of the present study was to investigate how the pandemic affected PHCWs as well as possible differences between PHCWs and other health care workers (OHCWs) in Germany during the first wave of the pandemic. We conducted a country-wide anonymous online survey early during the first pandemic wave between April 15th and May 1st, 2020, to assess different aspects of subjective burden and perceived stress using 5-point Likert-scale questions. We analysed data of 1530 PHCWs and 2114 OHCWs and showed that PHCWs reported higher subjective burden and stress compared to OHCWs (p<0.001). Overall, nurses from both groups of HCWs showed higher ratings in subjective burden and stress than physicians. These higher ratings for subjective burden were even more pronounced for nurses working in psychiatric hospitals. Future research is needed to investigate the causes for PHCWs’ increased stress and subjective burden, especially when taking into account the long-term effects of the pandemic, which may lead to further challenges and an ever-increasing workload, especially for PHCWs.
Keywords: healthcare workers; COVID-19; mental health; stress; psychiatry